2023
DOI: 10.1002/ajmg.a.63152
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variability and gastrointestinal manifestations/interventions for growth in NAA10‐related neurodevelopmental syndrome

Abstract: Our study of 61 children with NAA10‐related neurodevelopmental syndrome, an X‐linked disorder due to NAA10 gene variants, demonstrated a high prevalence of growth failure, with weight and height percentiles often in the failure‐to‐thrive diagnostic range; however, dramatic weight fluctuations and phenotypic variability is evidenced in the growth parameters of this population. Although never previously explored in depth, the gastrointestinal pathology associated with NAA10‐related neurodevelopmental syndrome in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…This current study continues our analysis of the original Naa10 -/Y knockout strain of live born mice, as previously reported [21], but now genetically inbred with more than 20 backcrosses phenotypic difference in body weight where the KO mouse is noticeably smaller than the WT littermate mouse. This is similar to the human condition, as some individuals with Ogden syndrome are small in weight and have short stature, whereas a few humans develop at typical size [53].…”
Section: Pleiotropic Effects Of Naa10 Knockout On Postnatal Micesupporting
confidence: 57%
See 1 more Smart Citation
“…This current study continues our analysis of the original Naa10 -/Y knockout strain of live born mice, as previously reported [21], but now genetically inbred with more than 20 backcrosses phenotypic difference in body weight where the KO mouse is noticeably smaller than the WT littermate mouse. This is similar to the human condition, as some individuals with Ogden syndrome are small in weight and have short stature, whereas a few humans develop at typical size [53].…”
Section: Pleiotropic Effects Of Naa10 Knockout On Postnatal Micesupporting
confidence: 57%
“…Previous publications have reported that one of the phenotypes observed in Naa10 knockout mice is low body weight compared to their wildtype littermates (Kweon et al 2021;Lee et al 2017). A recent analysis in humans analyzed these growth defects in greater detail, which showed extensive weight fluctuations, along with the recommendation that OS individuals not tracking above the failure to thrive range past one year of age might be considered for G-tube placement to avoid prolonged growth failure (Sandomirsky et al 2023). The current study aims to characterize the development, growth and phenotypes of various mice deficient in Naa10, beginning with embryogenesis, thus extending and expanding on our prior findings (Kweon et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Fig 8 shows a phenotypic difference in body weight where the KO mouse is noticeably smaller than the WT littermate mouse. This is similar to the human condition, as some individuals with Ogden syndrome are small in weight and have short stature, whereas a few humans develop at typical size [ 53 ].…”
Section: Resultsmentioning
confidence: 78%
“…Previous publications have reported that one of the phenotypes observed in Naa10 knockout mice is low body weight compared to their wildtype littermates [ 21 , 52 ]. A recent analysis in humans analyzed these growth defects in greater detail, which showed extensive weight fluctuations, along with the recommendation that OS individuals not tracking above the failure to thrive range past one year of age might be considered for G-tube placement to avoid prolonged growth failure [ 53 ]. The current study aims to characterize the development, growth and phenotypes of various mice deficient in Naa10 , beginning with embryogenesis, thus extending and expanding on our prior findings [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Six patients reported by the authors had precocious puberty. The study by Sandomirsky et al [15] of 61 children with Ogden syndrome, demonstrated a high prevalence of growth failure which was due to feeding difficulties in infancy, dysphagia, GERD/ silent reflux, constipation, diarrhea, bowel incontinence, eosinophilic esophagitis, cyclic vomiting syndrome, Mallory Weiss tears, abdominal migraine, esophageal dilation, and subglottic stenosis.…”
Section: Discussionmentioning
confidence: 99%